Total phenolic and total flavonoids content of pitaya peelss by water extraction - Ng, Wei Chet (2009)
Residues from the processing of fruits and vegetables which are traditionally considered an environmental problem is now widely recognized for obtaining high-phenolic products. This paper was designed to study the total phenolic and total flavonoids contents in the pitaya peels. The total phenolic content was determined by using the Folin-Ciocalteu assay while the total flavnoids was measured using aluminum chloride colorimetric assay by UV-visible spectrometer. The result showed that the highest total phenolic content in pitaya peels was extracted at the optimum dose of aluminum sulfate concentration of 25 mg/L (3.32 mg gallic acid equivalents (GAE)/ 25 g at 80oC, 3.21 mg GAE/25g at 60oC and 1.73 mg GAE/25g at 40oC). The greatest total flavonoids content in pitaya peels was extracted (2.24 mg catechin equivalents (CE)/25 g at 60oC, 1.79 mg CE/25g at 80oC and 1.60 mg CE/25g at 40oC) at the concentration of aluminum sulfate of 30 mg/L. The results showed that the value of the total phenolic content decreased when the concentration of aluminum sulfate of 25 mg/L due to the fact that the high concentration of aluminum sulfate (more than 25 mg/L) could have reacted with the phenolic compound of the pitaya peels to form another compound. The total flavonoid was found to be extracted with the highest value at temperature of 60oC and the lowest at 80oC. This shows that the flavonoids compound was somehow destroyed at temperature of 80oC.